Evaluation of Aqueous Extracts of Neem kernels and leaves for the control of spotted stem borer Chilo partellus Swinhoe, in sorghum at New Halfa, Sudan (Journal of Basic and Applied Research in Biomedicine, 2022)
A field experiment was conducted to study the effect of different concentrations of aqueous extracts of Neem kernels (NK) and Neem leaves (NL) on the incidence and damage of spotted stem borer in sorghum during 2011/12-2012/13 seasons at New Halfa Research Station farm. Sorghum variety Tabat was used. The experiment was laid in a RCB design with four replicates and seven treatments. These were: NK at kg/ 30 and 40 Liter of water, NL at kg/15 and 20 Liter of water, Furadan10% G at 15kg/F and Malathion 57% EC at 2L/F as standard and the untreated control. A liquid soap was added to Neem treatments as an emulsifying agent. Three sprayings were applied using knapsack sprayer starting two weeks after emergence with 10 days intervals. Data on percent deadheart, percent leaf damage plants, percent stem tunneling, number of borer holes per plant and grain yield were recorded. Results indicated that, all treatments were highly significantly (P>0.001)  reduced stem borer damage and increased the grain yield compared to the untreated one. NK at kg/ 40 L of water was the best in reducing stem borer damage and increasing grain yield comparable to the standard treatment Furadan 10% G at 15 Kg/F.